James Mallinson y Mark Singleton (trad., ed. e introd.), Roots of Yoga, Londres, Penguin Books, 2017, 540 pp. - Muñoz, Adrián (El Colegio de México, 2017)
James Mallinson and Mark Singleton (trans., ed. and introd.), Roots of Yoga, London, Penguin Books, 2017, 540 pp.